How Do Financing Constraints Affect Firms’ Equity Volatility? - CARVALHO, DANIEL (Journal of Finance, 2018)
ABSTRACT Theory suggests that financing frictions can have significant implications for equity volatility by shaping firms’ exposure to economic risks. This paper provides evidence that an important determinant of higher equity volatility among research and development (R&D)‐intensive firms is fewer financing constraints on firms’ ability to access growth options. I provide evidence for this effect by studying how persistent shocks to the value of firms’ tangible assets (real estate) affect their subsequent equity volatility. The analysis addresses concerns about the identification of these balance sheet effects and shows that these effects are consistent with broader patterns on the equity volatility of R&D‐intensive firms.